Daddy, Daddy, Can You Touch the Sky? - Kellerman, Jonathan; Kellerman, Jesse (New York : Bantam Books, 1994)
Six poems designed to develop strong identity concepts.
Something fishy - there's a monster in my closet - I'm me - What if - How to get rid of a ghost - daddy, daddy, can you touch the sky?
Grade level : 1 - 2
Keywords: Identity (Psychology) -- Juvenile poetry; Children's poetry, American; American poetry